Evidence That the Clinical Impairment Assessment (CIA) Subscales Should Not Be Scored: Bifactor Modelling, Reliability, and Validity in Clinical and Community Samples - Raykos, B.; Erceg-Hurn, D.; McEvoy, Peter; Byrne, S. (SAGE Publications, 2017)
Aim: The Clinical Impairment Assessment (CIA 3.0) is the most widely used instrument assessing psychosocial impairment secondary to eating disorder symptoms. However, there is conflicting advice regarding the dimensionality and optimal method of scoring the CIA. We sought to resolve this confusion by conducting a comprehensive factor analytic study of the CIA in a community sample (N = 301) and clinical sample comprising patients with a diagnosed eating disorder (N = 209). Convergent and discriminant validity were also assessed. Method: The CIA and measures of eating disorder symptoms were administered to both samples. Results: Factor analyses indicated there is a general impairment factor underlying all items on the CIA that is reliably measured by the CIA Global score. CIA Global demonstrated good convergent and discriminant validity. Conclusions: CIA Global is a reliable and valid measure of psychosocial impairment secondary to eating disorder symptoms; however, subscale scores should not be computed.